Assessment of dynamic behavior and seismic performance of a high-rise rc coupled wall building. (1st December 2018) - Kolozvari, Kristijan; Terzic, Vesna; Miller, Ross; Saldana, Daniel
Highlights: Development and validation of modeling approach for coupled wall systems. Code-based design of a 15-story archetype building. Dynamic analysis of coupled walls using axial-flexure-shear interaction model. Considerable shear-related damage in wall piers and slab-column connections. Interrupted functionality for several weeks for frequent earthquakes. Abstract: This study evaluates the seismic behavior and performance of a code-based high-rise RC coupled wall building located at the site with high seismicity representative of the West cost of the United States. Modeling approach for dynamic analysis of a coupled wall system is developed based on novel model for RC walls that captures nonlinear axial-flexure-shear (P-M-V) interaction and is validated using detailed experimental data available in the literature, providing the opportunity to analyze the behavior of this system from the new perspective. Seismic performance assessment is conducted considering structural and nonstructural building components based on two performance metrics: repair cost and repair time. The loss metrics are evaluated using FEMA P-58 methodology in conjunction with a realistic repair time model considering frequent (50% in 50 years), rare (10% in 50 years), and very rare (2% in 50 years) earthquake events. Analysis results reveal that strong ground shaking causes significant variation of axial forces in piers of the coupled wall system resulting in P-M-V interaction and considerable shear-related damage (cracking) over most of the wall height, while coupling beam rotations and corresponding damage are relatively small due to their excessive capacity obtained from the code-based design. Although median repair cost is relatively low, less than 6% of construction cost for frequent and rare earthquakes and about 24% for very rare earthquakes, building functionality is impaired at all hazard levels ranging from few weeks for frequent earthquakes to several months for very rare earthquakes, predominantly driven by damage to wall piers and slab-column connections.